Determinants of the Adoption of Digital Finance: Evidence from Indonesia - Dewi, Vera Intanie; Debby, Teressia; Dharwiyanti, Sri (ETIKONOMI, 2026)
Research Originality: This study offers novelty by analyzing the underexplored influence of customer-perceived value on the intention to use digital finance, and how this relationship is uniquely moderated by digital financial literacy and perceived risk. Research Objective: The research investigates the effect of the customer value proposition on the intention to use digital finance, and whether this relationship is strengthened by digital financial literacy and the perceived risk. Research Method: Using a quantitative explanatory design, the data from 409 Indonesian respondents were analyzed employing PLS-SEM. Empirical Results: The findings indicate that convenience, economic benefits, security, and seamless transactions significantly enhance CPV, which in turn positively affects the intention to use digital finance. DFL strengthens the relationship between CPV and the intention to use digital finance (quasi-moderator), whereas the perceived risk weakens it (pure moderator). Implication: These results imply that strengthening the value propositions, improving people’s digital financial literacy, and mitigating the perceived risk are critical strategies to accelerate the responsible adoption of digital finance in emerging economies. JEL Classification: O33, G20, G53, D14, D91